Noninvasive Diagnosis of Bladder Cancer by Detection of Matrix Metalloproteinases (MMP-2 and MMP-9) and Their Inhibitor (TIMP-2) in Urine - Eissa, Sanaa; Ali-Labib, Randa; Swellam, Menha; Bassiony, Manal; Tash, Fathy; El-Zayat, Tarek Mostafa (European urology, 2007)
TIMPs control the activity of MMPs, one of the key molecules for tumor invasion and metastasis. The aim of this study was to assess the usefulness of MMP-2 and MMP-9 in relation to their inhibitor (TIMP2) as noninvasive diagnostic tests for bilharzial bladder cancer. Voided urine samples were provided from 244 subjects (154 bladder cancer [136 bilharzial]; 60 benign urologic disorders; 30 healthy volunteers). Urine sediment was used for cytology, and the supernatant for estimation of MMPs and TIMP-2 by ELISA and gelatin zymography. The best cut-off values for the investigated markers were determined by ROC curve. Positivity rates and median levels for MMP-2, MMP-9, TIMP-2, MMP-2/TIMP-2, and MMP-9/TIMP-2 showed significant difference among the three investigated groups (p<0.001). MMP-9 and MMP-2/TIMP-2 were related to pathologic type, MMP-2/TIMP-2 was inversely related to the grade, and MMP-9/TIMP-2 was related to bilharziasis (p<0.05). MMP zymography results were comparable to those from ELISA. The sensitivity and specificity of MMP zymography, MMP-9/TIMP-2 ratio, and MMP-2/TIMP2 ratio were superior among all investigated parameters; furthermore, combined testing of cytology with them improves the sensitivity even in superficial and low-grade tumors. Urinary MMP-2 and MMP-9 and TIMP-2 and their ratios were assessed in 154 bladder cancer cases, 60 benign bilharzial urological lesions and 30 healthy controls. The sensitivity of cytology improved when combined with either ratio especially in superficial and low-grade tumors.